Penapisan Galur Haploid Ganda Padi Gogo Hasil Kultur Antera untuk Toleransi terhadap Cekaman Aluminium - , Bakhtiar; Bambang S. Purwoko; , Trikoesoemaningtyas; M. A. Chozin (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
Aluminum (Al) toxicity is one of the most important yield-limiting factors for upland rice grown on acid soils. Since many small farmers may have difficulty in soil liming, the genotypes tolerant to soil acidity and aluminum toxicity should be developed. Anther culture can substantially speed up new variety development through recombination of parental characters in early generations and immediately homozygous lines were upon chromosome doubling. The Doubled haploid (DH) rice lines were screened under both nutrient solution containing either 0 or 45 ppm Al and acid soils containing either low or high-Al saturation. The relative root length (RRL) was determined at 14-day-old stage to characterize genotypes for Al-tolerance in nutrient solution. The relative grain weight (RGW) was determined to characterize genotypes for Al-tolerance in soils conditions. The results of this study indicated that Al reduced root elongation. The differential tolerance for Al among genotypes was found to be highly significant for RRL. Of the 120 genotypes tested, 16, 77 and 27 genotypes were found to be Al-tolerance, moderate and sensitive in term of RRL respectively. KRGM4, JTGR13, JTGR17, JTGR18, JTKR1, JTKR5, GRGM4, GRGM6, GRGM9, GRGM14, GRGM25, GRJT11 and SGJT27 lines were consitently Al-tolerance under both nutrient solution and acid soils. The RRL of doubled haploid upland rice lines in nutrient solutions were strongly correlated with RGW in acid soils. Key words: Rice, doubled haploid, aluminum tolerance, relative root length, relative grain weight